Optimization of Outer Diameter Bernoulli Gripper with Cylindrical Nozzle - Roman Mykhailyshyn; František Duchoň; Ivan Virgala; Peter Jan Sinčák; Ann Majewicz Fey (Machines, 2023)
Gripping and manipulating objects using non-contact and low-contact technologies is becoming increasingly necessary in manufacturing. One of the promising contactless gripping technologies is Bernoulli gripping devices for industrial robots. They have many advantages, but when changing the nozzle geometry, it is difficult to find the optimal parameters of the outer diameter of the gripper and its operating parameters. Therefore, the article presents a model for numerical simulation of the dynamics of airflow in the nozzle of the Bernoulli gripping device and in the radial gap between its active surface and the surface of the object of manipulation. Reynolds-averaged Navier–Stokes equations of viscous gas dynamics, SST-model of turbulence, and γ-model of laminar-turbulent transition were used for this purpose. The technical requirements for the design of the nozzle of Bernoulli jet gripping nozzles are determined and variants of their constructive improvement are offered. According to the results of numerical simulation in the Ansys-CFD software environment, the optimal diameter of the Bernoulli gripping device and the influence of the geometric parameters of the nozzle on the nature of the pressure distribution in the radial gap and its lifting force were determined. Determined the optimal parameters of the height of the gap between the object of manipulation and the Bernoulli gripping device using C—Factor, which will allow efficient operation of Bernoulli gripping devices during automated handling operations using industrial robots.